Karakter Morfologis dan Ekologis Coffea arabica L. di Perkebunan Rakyat dan Perhutani Pandansari Malang: Morphological and Ecological Characters of Coffee Arabica L. in the People's and Perhutani Plantation of Pandansari, Malang - Shalehah, Nikmatus; Hakim, Luchman; Zayadi, Hasan (FMIPA UNISMA, 2024)
The conditions in which plants grow affect plant growth and development. If the conditions in which the plant grows are not suitable, its growth will be disrupted and the yield of plant production is not optimal. This research was carried out in two locations, namely in Perhutani land with an altitude of 1110 meters above sea level and community plantations with an altitude of 914 meters above sea level. The type of research used is descriptive qualitative with exploratory sampling. The results showed that ecological factors affect plant morphology. Different light intensities cause the leaves on smallholder plantations to be smaller in size to reduce water evaporation and the distance between the segments of Coffea arabica L. on perhutani land has a longer internode distance due to etiolation. The shade trees found in smallholder plantations are Maesopsis eminii, Engl., Leucaena leucocephala subsp. Glabrata, Pterocarpus indicus, Hibiscus tiliaceus, Toona sureni, Melia azedarach, Leucaena leucocephala. The shade trees on Perhutani land are Pinus merkusii and Ficus benjamina L. Keywords: morphology, ecology, Coffea arabica L, shade trees. ABSTRAK Kondisi tempat tumbuh tanaman mempengaruhi pertumbuhan dan perkembangan tanaman. Apabila kondisi tempat tumbuh tanaman tidak sesuai maka pertumbuhannya akan terganggu dan hasil produksi tanaman tidak maksimal. Penelitian ini dilaksanakan di dua lokasi yaitu di lahan perhutani dengan ketinggian 1110 m dpl dan perkebunan rakyat dengan ketinggian tempat 914 m dpl. Jenis penelitian yang digunakan adalah kualitatif deskriptif dengan pengambilan sampel secara eksplorasi. Hasil penelitian menunjukkan bahwa faktor ekologi mempengaruhi morfologi tanaman. Intensitas cahaya yang berbeda menyebabkan daun di lahan perkebunan rakyat berukuran lebih kecil untuk mengurangi penguapan air dan jarak antar ruas pada Coffea arabica L. di lahan perhutani memiliki ukuran antar ruas lebih panjang karena etiolasi. Pohon penaung yang terdapat di lahan perkebunan rakyat adalah Maesopsis eminii, Engl., Leucaena leucocephala subsp. Glabrata, Pterocarpus indicus, Hibiscus tiliaceus, Toona sureni, Melia azedarach, Leucaena leucocephala. Pohon penaung di lahan perhutani adalah Pinus merkusii dan Ficus benjamina L. Kata kunci: morfologi, ekologi, Coffea arabica L, pohon penaung.